Risk Factors and Challenging Management of Lung Adenocarcinoma in Young Adult Women: Case Series - Ida Ayu Jasminarti Dwi Kusumawardani; Luh Komang Ayu Widhiaty Karang; Ni Wayan Candrawati; Herman Saputra; Ni Putu Sriwidyani; Nornazirah Binti Azizan (Jurnal Respirasi, 2022)
Introduction: Lung cancer found in young age is relatively rare with a percentage of cases only 1.4% of overall lung cancer cases in the world. Case: We reported two cases of lung adenocarcinoma in young women aged less than 30. The first case was lung adenosquamous carcinoma in a 28-year-old woman, a passive smoker, who had a family history of cancer. She had the mutation of epidermal growth factor receptor (EGFR) exon 19 deletion and received 1st generation of tyrosine kinase inhibitor. Since the patient was diagnosed at advanced stage with poor performance status, she died within 2 months after being diagnosed. The second case was lung adenocarcinoma in a 23-year-old woman. The patient was a passive smoker and had a history of cancer in the family. She was diagnosed at an advanced stage but with good performance status. The patient underwent chemotherapy with Pemetrexed-Platinum in 6 cycles and 15 cycles of radiotherapy. Conclusion: Lung cancer at a young age is more common in non-smoking female with the histopathology type adenocarcinoma. Non-specific early symptoms become a problem in the early enforcement of lung cancer at a young age. Many cancer-related issues occur in young cancer patient such as premature death, increased dependence on parents, difficulty in school and work due to medication, and reproductive disturbance.